2015
DOI: 10.1515/ijafr-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carrot puree edible films on quality preservation of fresh-cut carrots

Abstract: The effect of edible films based on carrot puree, chitosan, corn starch, gelatin, glycerol and cinnamaldehyde on freshcut carrots was studied during storage. Several parameters, such as firmness, colour, weight loss, total carotenoids, total phenols, polyphenol oxidase (PPO) activity and peroxidase (POD) activity in coated carrots were determined at regular intervals and then compared with the uncoated carrots throughout the storage period. Significant and expected changes were observed in all carrot samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…have reported that the color maintenance of fresh‐cut carrots associated with heat treatment correlated well with POD activity level. Whitening inhibition of fresh‐cut carrots by ozone in synergy with controlled atmosphere storage and edible films correlated well with POD and PPO inhibition. The results of the present study are consistent with these reports, where WI was significantly and positively correlated with PPO and POD activities ( r = 0.642–0.725).…”
Section: Discussionmentioning
confidence: 74%
“…have reported that the color maintenance of fresh‐cut carrots associated with heat treatment correlated well with POD activity level. Whitening inhibition of fresh‐cut carrots by ozone in synergy with controlled atmosphere storage and edible films correlated well with POD and PPO inhibition. The results of the present study are consistent with these reports, where WI was significantly and positively correlated with PPO and POD activities ( r = 0.642–0.725).…”
Section: Discussionmentioning
confidence: 74%
“…The uselessness of emulsion coating in controlling WL of cold‐stored fresh‐cut vegetables has been observed previously (Kowalczyk, Pikula, & Baraniak, ). Nevertheless, many studies have demonstrated the beneficial effect of coating on reduced moisture loss of MPFV (Kowalczyk & Pikula, ; Kraśniewska et al, ; Wang, Kong, Ma, & Zhao, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many studies have demonstrated the beneficial effect of coating on reduced moisture loss of MPFV Kraśniewska et al, 2016;Wang, Kong, Ma, & Zhao, 2015).…”
Section: As Shown Inmentioning
confidence: 99%
“…In another patent, gelatin and glucomannan films with garlic juice were described as antimicrobial and favouring agents (CN 103589168A patent) [114]. Other vegetables and fruits recently reported to be coated or wrapped with gelatin-based films and coatings are carrots [115], cherry tomatoes [116], calyx from physalis [117], oranges [118], banana and eggplant epicarps [119], fresh-cut melons [120], peppers [121], strawberries [122], blueberry fruit [123], pineapple fruit [124] and minimally processed persimmon [125].…”
Section: Other Food Productsmentioning
confidence: 99%